DAMPAK KONVERSI LAHAN SAWAH DI JAWA TERHADAP PRODUKSI BERAS DAN KEBIJAKAN PENGENDALIANNYA - BAMBANG IRAWAN; SUPENA FRIYATNO (SOCA: Jurnal Sosial Ekonomi Pertanian, 2002)
The scarcity of land, especially sawah land is one of problems that cause to achieve riceproduction more difficult for producing the staple food. Because of that, the Indonesianstatus shifted from self sufficient to rice importer. The objective of this paper is to seekthe size of sawah land conversion and how is the implication to the rice production, andhow is the Government effort to control the sawah land conversion. By tabulation andsimple mathematic approach, the result showed that during 18 years 26, 9 thousandhectares each year, occurred net sawah conversion in Java. During that period, netaccumulation of rice losses was about 40, 6 million ton or 2, 2 million ton per year as animpact of sawah land conversion. The government effort to control sawah landconversion just conducted by law enforcement approach, which is still looking for thebest way. So, the effectiveness of law enforcement to control sawah land conversion isstill relatively low.